Assessing the Nursing Workload in the Cardiothoracic Intensive Care Unit: Comparative Study - Natasa Stojakovic; Aleksandra Matic; Andrej Preveden; Milenko Rosic; Milena Mikic; Vesna Rosic; Visnja Mihajlovic (Nursing Open)
ABSTRACT Aims This study aimed to assess nursing workload in Cardiac Intensive Care Unit (CICU) after three cardiothoracic surgery procedures during first four postoperative days using Nursing Activities Score (NAS) and Nine Equivalents of Nursing Manpower Use Score (NEMS) systems, to compare their performance for that purpose and to investigate association between nursing workload and type of surgery. Design A comparative study. Methods The research environment includes CICU of the University Hospital for Cardiovascular Diseases in Serbia. A total of 808 patients who underwent coronary, valvular, or combined surgery, resulting in 2282 filled NAS and NEMS pairs chart. Statistical analysis was performed using SPSS‐19. The correlation between NAS and NEMS was tested by Spearman's correlation coefficient. Differences were considered statistically significant at p < 0.05. Results The lowest median of cumulative NAS 176 (175‐257) and NEMS 76 (64‐91) had coronary surgery patients, the highest NAS 224.5 (178‐334.5) and NEMS 83 (69‐121) had those with combined surgery; this difference was statistically significant (p < 0.001). The median of both scores decreased after surgery, with the following values from the first to the fourth postoperative day: NAS from 104 (102‐105) to 81 (74‐85) and NEMS from 46 (42–46) to 30 (30–37). The difference in mean values of both scores between the first and the fourth postoperative day was statistically significant (p < 0.001). NAS and NEMS were in a positive, strong correlation (r = 0.913; p < 0.005). Conclusion Both scores can be used to measure nursing workload, identify the required number of nurses in CICU, and support task allocation. NAS may have an advantage because it better describes extensive postoperative monitoring and care needed for cardiac surgery patients. Nursing workload is associated with type of surgery, with the highest workload measured in patients who underwent combined surgery procedure and on the first postoperative day.